2021
DOI: 10.3390/jcm10153225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multimorbidity on Fragility Fractures in Community-Dwelling Older Adults: Shimane CoHRE Study

Abstract: Fragility fractures (FFxs), which are a common musculoskeletal injury in older adults, is associated with an increased frequency of falls. Both FFxs and falls may result from drugs, habits, and co-occurring diseases. We aimed to evaluate the effects of various diseases on the risk of FFx. This retrospective study included 1420 individuals aged ≥60 years. We evaluated the history of clinical FFx and diseases using a detailed questionnaire and a health examination. The risk of comorbidities was assessed using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Furthermore, anti-epileptic and steroid use may be involved in bone fragility among patients with rheumatoid arthritis and epilepsy. Therefore, together with other studies [ 30 - 32 ], the results of our study through multivariate regression analysis showed that patients using steroids and anti-epileptics are at a higher risk of vertebral fragility fractures.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, anti-epileptic and steroid use may be involved in bone fragility among patients with rheumatoid arthritis and epilepsy. Therefore, together with other studies [ 30 - 32 ], the results of our study through multivariate regression analysis showed that patients using steroids and anti-epileptics are at a higher risk of vertebral fragility fractures.…”
Section: Discussionsupporting
confidence: 81%
“…Set 1 and Set 2 consisted of 1014 and 841 participants. Both were from Shimane CoHRE Study 20 , 21 , but different arrays were used for genotyping. Set 3 consisted of 1623 participants from Bunkyo Health Study 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Bunkyo Health Study is a prospective cohort study of over 10 years 21 , which recruited older subjects aged 65–84 years living in Bunkyo-Ku, an urban area in Tokyo, Japan. Among the 68 communities in Bunkyo-Ku, we selected 13 communities based on probability proportionate to size sampling.…”
Section: Methodsmentioning
confidence: 99%
“…Set 1 and Set 2 consisted of 1,014 and 841 participants. Both were from Shimane CoHRE Study 19,20 , but different arrays were used for genotyping. Set 3 consisted of 1,623 participants from Bunkyo Health Study 21 .…”
Section: Resultsmentioning
confidence: 99%
“…This cross-sectional study is a part of the cohort study conducted by the Center for Community-based Healthcare Research and Education in Shimane University (Shimane CoHRE Study) 19,20 . Shimane CoHRE Study is an ongoing health examination for the community-dwelling people in Shimane prefecture, Japan.…”
Section: Shimane Cohre Studymentioning
confidence: 99%